1999
DOI: 10.1017/s0012162299001413
|View full text |Cite
|
Sign up to set email alerts
|

Outcome at 1 year of neonatal encephalopathy in Kathmandu, Nepal

Abstract: To determine the outcome at 1 year of neonatal encephalopathy (NE) and to estimate the possible contribution of birth asphyxia to childhood disability in a low-income South Asian country, a prospective cohort study was undertaken in the principal maternity hospital of Kathmandu, where over 50% of local women give birth. From a total population cohort of 21609 live births, 131 term infants with NE (after exclusion of cases associated with neonatal sepsis, congenital malformations, or primary hypoglycaemia) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 29 publications
3
22
1
Order By: Relevance
“…Zambian study has shown that there is four times more chance of having abnormal neurologic outcome in infants who have asphyxia at birth 8 . Similar study in Kathmandu has also shown that newborns who were asphyxiated and had encephalopathy at birth, 28% developed cerebral palsy 9 . Prematurity is another important risk for developing developmental disabilities.…”
supporting
confidence: 67%
“…Zambian study has shown that there is four times more chance of having abnormal neurologic outcome in infants who have asphyxia at birth 8 . Similar study in Kathmandu has also shown that newborns who were asphyxiated and had encephalopathy at birth, 28% developed cerebral palsy 9 . Prematurity is another important risk for developing developmental disabilities.…”
supporting
confidence: 67%
“…In a study of newborn infants with severe encephalopathy in Nepal, mortality was 97%. 24 In addition, 74% of the survivors who had moderate encephalopathy during the neonatal period and 26% of the survivors who had mild encephalopathy had abnormal neurodevelopmental outcomes at 1 year. Almost 50% of the babies included in the current study were born at home.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to their chronic nature and tendency to cause disability, handicaps and loss of potential of the affected child [1]. The psychosocial and/or financial burden and stigmatization to the affected child and the family can be enormous [2,3].…”
Section: Introductionmentioning
confidence: 99%